UPAYA PEMBIASAAN KARAKTER ISLAMI PADA ANAK KELOMPOK B USIA 5-6 TAHUN DI RAUDHATUL ATHFAL TARBIYATUSH SHIBYAN KABUPATEN MALANG - Nurul Hidayati; Khoirul Asfiyak; Ika Anggraheni (Jurnal Dewantara, 2019)
Conditions that occur in Raudhatul Atfhal Tarbiyatush Shibyan still have some children who behave in a bad manner and are not polite like saying harsh words and shouting, behavior that is not good like going up on a table that does not reflect Islamic character in children. This study aims to find a solution to the habituation of Islamic characters in group B children aged 5-6 years in RA Tarbiyatush Shibyan Malang Regency. This research is a field research qualitative research approach with a type of case study research. Data collection methods used include Observation Method, Interview Method and Documentation Method. The technical analysis of data uses data reduction, data presentation and conclusion or verification. While checking the validity of the data using source triangulation, technique triangulation and time triangulation. The implementation of the Islamic character habituation program to children in addition to being implemented in institutions / schools namely RA Tarbiyatush Shibyan is also within the home environment of students.               The result of the habituation of Islamic character to children in RA Tarbiyatush Shibyan is to show that the planning carried out by the teacher at RA Tarbiyatush Shibyan in an effort to habituate Islamic characters to children includes, developing vision and mission, arranging rules, compiling daily, weekly, monthly / annual work programs and anecdotal notes. The implementation uses various strategies, namely habituation, giving examples with reproduction, always reminding and giving educational sanctions to children. While group B teacher monitoring / evaluation includes: getting used to pray before and after activities, getting used to memorizing daily prayers, short letters and simple hadiths, getting used to always saying and acting well and politely, getting used to always doing good, honest and responsible , Getting used to always follow the rules, getting used to following the procedures of prayer with movement and memorizing the reading, and getting used to always say thoyyibah sentences.